Complex liver resection under hepatic vascular exclusion and hypothermic perfusion with versus without veno-venous bypass: a comparative study. Issue 9 (September 2019) - Navez, Julie; Cauchy, François; Dokmak, Safi; Goumard, Claire; Faivre, Evelyne; Weiss, Emmanuel; Paugam, Catherine; Scatton, Olivier; Soubrane, Olivier
Abstract: Background: While hypothermic liver perfusion has been shown to improve parenchymal tolerance to complex resections in patients requiring prolonged hepatic vascular exclusion (HVE), the benefit of associated veno-venous bypass (VVB) in this setting remains poorly evaluated. Methods: All patients undergoing liver resection requiring HVE and hypothermic liver perfusion for at least 55 min between 2006 and 2017 were retrospectively reviewed. Perioperative outcomes were compared between patients with (VVB+) or without VVB (VVB−). Results: Twenty-seven patients were analyzed, including 13 VVB+ and 14 VVB−. Median HVE duration was similar in VVB+ and VVB− patients (96 vs. 75 min, respectively). VVB+patients had longer operative time (460 vs. 375 min, p = 0.023) but less blood loss (p = 0.010). Five (19%) patients died postoperatively from liver failure or sepsis, without difference between groups. Postoperative major morbidity rate was similar between VVB+ and VVB− patients (30% vs. 50%, respectively) such as rates of liver failure, haemorrhage, renal insufficiency and sepsis, but VVB− patients experienced more respiratory complications (64% vs. 15%, p = 0.012). Conclusion: During liver resection under HVE and hypothermic liver perfusion, use of VVB allows for reducing blood loss and postoperative respiratory complications. VVB should be recommended in case of liver resection with prolonged HVE.